FISHER FOLK: SOCIAL AND GEOGRAPHICAL SPACES OF MARGINALITY - Muhammed Swalih P (GLOBAL JOURNAL FOR RESEARCH ANALYSIS, 2019)
Kerala state marked distinct from all other indian state with its unique model of development. Contrary to this State Development Report 2011 followed by subsequent studies and works of many scholars projected 'Outlier communities'; the communities who are left out of the state achievements in development indices and placed far behind the state average - Tribals and Fishermen. Considering the outlier position of shing communities despite many development programmes and projects implemented for the sake of development of shing communities at central and state levels; the outlier position of shing communities still remain unaddressed and the community remains at the margin of development. This paper attempts to trace this crucial issue of marginalisation through the concept of 'Space' which has social, political, economic and geographical connotations.